2017
DOI: 10.1097/md.0000000000007056
|View full text |Cite
|
Sign up to set email alerts
|

Adjacent segmental degeneration following Wallis interspinous stabilization implantation

Abstract: Adjacent segmental degeneration (ASD) is a major issue after pedicular fixation. This study examined the degeneration of the adjacent levels due to the insertion of the Wallis interspinous stabilization system compared with discectomy, using magnetic resonance imaging (MRI).Thirty-eight patients diagnosed with lumbar degeneration disorders at L4-L5 were reviewed: 19 patients underwent discectomy and Wallis system implantation (group A), and 19 patients underwent discectomy (group B). The Visual Analog Scale (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…reported that PLIF increased torsional rigidity compared with Coflex, placing a higher load burden on the adjacent disc and facet joint in rotational activity [22] . Likewise, the Wallis implant consists of an interspinous spacer and two bands to secure the implant in the interspinous space and limit flexion and extension [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…reported that PLIF increased torsional rigidity compared with Coflex, placing a higher load burden on the adjacent disc and facet joint in rotational activity [22] . Likewise, the Wallis implant consists of an interspinous spacer and two bands to secure the implant in the interspinous space and limit flexion and extension [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%